GAYA KEPEMIMPINAN YANG DIINGINKAN KARYAWAN (Studi pada Badan Pengembangan Sumber Daya Manusia Daerah Provinsi Jawa Tengah) - Marpaung, Levina; Mas’ud, Fuad (Diponegoro Journal of Management, 2017)
Culture in a country has a close relationship to leadership in the country. The man is a leader for himself. Every human being has the desired leadership criteria. This research will discuss what kind of lead character the employee wants.The purpose of this research is to investigate what kind of leadership style desired by employees at Badan Pengembangan Sumber Daya Manusia Daerah Provinsi Jawa Tengah. The method used is a qualitative method with phenomenology study approach, in which data collection is done by interview, observation, and documentation in a certain period. Methods are chosen on the grounds that research can be done in a more focused and in-depth manner.The results of this research indicates that the leadership desired by the employees is the leadership that gives the form of attention outside the work affairs, the leader who want to go down directly, embrace, democratic, listen to the voice of the staff, walk according to existing rules, and want to familiarize themselves with the staff .